Nuances da visão evangélica dos direitos humanos - Oliveira Jr, Humberto Ramos de (2022)
This investigative work focuses on the performance of evangelical parliamentarians active in the National Congress in relation to human rights agendas. This group of evangelicals has acted strongly by vetoing and obstructing bills and public policies aimed at the so-called “political minorities”, becoming an important and controversial subject in the national political scenario. In contrast, the initiatives of other evangelicals working in the defense of human rights, mainly driven by the values of ecumenism, are also analyzed. The thesis addressed different perceptions in the evangelical environment regarding human rights and how they translate into certain relevant actions, seeking evangelical dissonances regarding the theme of human rights. The research was developed by reviewing the available bibliography on the subject, analyzing documents produced by those involved - such as videos, books, websites and interviews - and, finally, systematized an observation of events with political incidence of the group in focus.